Catalytic hydrodeoxygenation of guaiacol and its application in bio-oil upgrading - TRAN , THI TO NGA (2018)
Fast pyrolysis of lignocellulosic biomass is an attractive thermochemical conversion process to produce bio-oil as an alternative liquid fuel source. Upgrading of bio-oil via hydrodeoxygenation (HDO) is an important route to accomplish this renewable energy production process. However, there are still some challenges such as high hydrogen consumption, carbon loss, catalyst deactivation, complex reaction network, and limitation in upgrading of real bio-oil.